Upaya Meningkatkan Hasil Belajar Keterampilan Passing Bawah Bola Voli Melalui Metode Bermain - Bayu Pangestu; Iif Firmana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the learning outcomes of underhand passing skills through the application of play-based methods to fifth and sixth grade students at SDN 1 Bumijawa. This study used a quantitative approach with a One Group Pretest and Posttest experimental design. The sample in this study was 15 students. Data were collected through underhand passing skills tests conducted before and after treatment. The results showed a significant increase in underhand passing skills after students participated in learning using the play-based method. This method has been proven to be able to increase students' interest, active participation, and understanding of basic volleyball techniques. In addition, the application of the play-based method also creates a more enjoyable learning atmosphere and reduces student boredom. This method directly involves students in practical activities, so that students not only understand the theory but also can apply it in real games. Play activities carried out in small groups allow students to learn from each other and increase self-confidence. Improvement in underhand passing skills also shows that the play-based method is effective in developing fine motor skills needed in volleyball. Therefore, the play-based method can be used as an alternative strategy in learning Physical Education, especially volleyball material in elementary schools. This study suggests that Physical Education teachers implement play-based methods more widely to maximize student learning and learning outcomes, as well as increase their motivation and enthusiasm for sports. Furthermore, implementing play-based methods can also improve teamwork among students, a crucial aspect of volleyball. With a more fun and interactive approach, students are more motivated to practice and master the skills taught.